2009
DOI: 10.1016/j.juro.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Role of a Folkloric Medicinal Plant Extract in a Rat Partial Nephrectomy Model: Controlled Experimental Trial

Abstract: Ankaferd BloodStopper decreases partial nephrectomy and warm ischemia times, and provides hemostasis. Erythrocyte aggregation confirmed the hemostatic action of the agent, while the absence of glomerular necrosis and calcification may have positive relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 16 publications
5
38
0
1
Order By: Relevance
“…Numerous studies reported the hemostatic effects of topical ABS in the animals with normal [10,12,14,[16][17][18] and defective hemostasis [15,24], and have set the preclinical stage for the development of this hemostatic product. The effects of ABS on hemostatic parameters have also been searched [2,6,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies reported the hemostatic effects of topical ABS in the animals with normal [10,12,14,[16][17][18] and defective hemostasis [15,24], and have set the preclinical stage for the development of this hemostatic product. The effects of ABS on hemostatic parameters have also been searched [2,6,25].…”
Section: Discussionmentioning
confidence: 99%
“…The hemostatic effects of ABS have been observed in vitro and in vivo [12][13][14][15][16][17][18]. Use of ABS as a hemostatic agent in external hemorrhages and in dental treatment in humans provided the first data showing that ABS was safe and effective in humans [9].…”
Section: Introductionmentioning
confidence: 99%
“…Topical hemostatic efficacy of ABS has been previously tested in animals with normal [2,5] and defective hemostasis [3,6]. Short-term hematological and biochemical safety of the oral systemic administration of Ankaferd to rabbits has been shown [20].…”
Section: Discussionmentioning
confidence: 99%
“…Topical safety of ABS in normal healthy human volunteers was shown in a randomized double-blind cross-over Phase I clinical trial after preclinical animal studies [2][3][4][5][6]. ABS has been approved for local topical applications in external post-surgical and post-dental surgery bleedings in Turkey (www.Ankaferd.com).…”
Section: Introductionmentioning
confidence: 99%
“…Those findings are compatible with the previous studies by Huri et al testing topical ABS in the in the partial nephrectomy and renal trauma models. [18][19][20] Essential erythroid proteins (Ankrin recurrent and FYVE bundle containing protein 1, Spectrin alpha, Actin-depolimerisation factor, Actin-depolimerizing factor, LIM bundle and actine binding subunit 1 isoform a, LIM bundle and actine binding subunit 1 isoform b, NADP-dependent malic enzyme, NADH dehydrogenase (Ubiquinone) 1 alpha subcomplex, Mitochondrial NADP (+) dependent malic enzyme 3, Ribulose bisphosphatecarbocsilase large chain, Maturase K) and the required ATP bioenergy (ATP synthase, ATP synthase beta subunit, ATP synthase alpha subunit, ATP-binding protein C12, TP synthase H+ transporter protein, ADF, Alpha-1,2-glycosyltransferase ALG10-A) are included in the protein library of ABS. ABS also up-regulates GA-TA/FOG transcription system affecting erythroid functions and urotensin II.…”
Section: Discussionmentioning
confidence: 99%